2020
DOI: 10.1515/ntrev-2020-0110
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of functionally graded carbon nanotube-reinforced composite structures: A review

Abstract: Functionally graded carbon nanotube-reinforced composite (FG-CNTRC) is a novel nanomaterial; the mechanical behavior of FG-CNRC has become a hot topic in the Materials Science and Engineering Science recently, thanks to its excellent mechanical and electrical properties after its fusion with matrix. In this paper, the review efforts for research progress on the modeling and analysis of FG-CNTRC structures are carried out. Firstly, the development background of FG-CNRC is presented, as well as some basic theori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…Desirable wound dressings must have excellent mechanical properties to maintain integrity during the treatment period and to withstand the forces applied, which are mainly tensile rather than compressive. Therefore, tensile tests were carried out to determine the stretchability of wound dressings of various compositions Figure S2 demonstrates the stress–strain curves of the pure electrospun PA6 nanofibers and the electrospun PA6/PVA nanofibrous composite loaded with different amounts of CMWCNT-Cur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Desirable wound dressings must have excellent mechanical properties to maintain integrity during the treatment period and to withstand the forces applied, which are mainly tensile rather than compressive. Therefore, tensile tests were carried out to determine the stretchability of wound dressings of various compositions Figure S2 demonstrates the stress–strain curves of the pure electrospun PA6 nanofibers and the electrospun PA6/PVA nanofibrous composite loaded with different amounts of CMWCNT-Cur.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, tensile tests were carried out to determine the stretchability of wound dressings of various compositions. 53 Figure S2 demonstrates the stress−strain curves of the pure electrospun PA6 nanofibers and the electrospun PA6/PVA nanofibrous composite loaded with different amounts of CMWCNT-Cur. Also, in Table 1, the data obtained from the stress−strain curves of these nanofibers are tabulated.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Here 'L' represents length of beam, 'b' the width and 'h' the thickness of FG beam. The top surface of the FG beam is combined with piezoelectric material layer having length L p and thickness h p. The volume fraction is defined as follows (figure 1(b)) [5]:…”
Section: Model Developmentmentioning
confidence: 99%
“…They observed that volume fraction of CNT is significantly influencing the bending deflection as well as natural frequency. Zhang et al [5] published a review on studies of FGCNT reinforced structures. Jia et al [6] examined the mechanical and electrical behaviour of FG beams using couple stress theory and observed that when applied voltage decreases, the buckling temperature increases with increased volume fraction of CNT.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the discovery of CNTs has increased their popularity, as well as the availability of nanocomposites. Today, among the nanocomposites formed by the reinforcement of the main matrix with carbon nanotubes, polymer-based nanocomposites are more popular than metal and ceramic-based nanocomposites, and are used more frequently in various industries [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%